Contemporary intrastate conflicts : An approach to its structural causes - Guerrero Sierra, Hugo F. (Universidad de La Salle. Revistas. Equidad & Desarrollo., 2012)
The proposal of this paper is to present a conceptual analysis on the phenomenon of social conflict, specifically when it leads to dynamics of violent order. Similarly, once this conceptual clarification is established, and through reference to particular cases, a brief overview is presented of different contributions that have been made from the world of academia regarding the connection between the phenomenon of intrastate conflicts and its possible structural causes.